Laparoscopic restorative proctocolectomy with ileal-J-pouch anal canal anastomosis without diverting ileostomy for total colonic and extensive aganglionosis is safe and feasible with combined Lugol's iodine staining technique and indocyanine green fluorescence angiography - Nakagawa, Yoichi; Yokota, Kazuki; Uchida, Hiroo; Hinoki, Akinari; Shirota, Chiyoe; Tainaka, Takahisa; Sumida, Wataru; Makita, Satoshi; Amano, Hizuru; Takimoto, Aitaro; Ogata, Seiya; Takada, Shunya; et al. (Frontiers in Pediatrics, 2023)
Background: We present the surgical technique and outcomes of reduced-port laparoscopic restorative proctocolectomy with ileal-J-pouch anal canal anastomosis (IPACA) without diverting ileostomy for total colonic and extensive aganglionosis (TCA+). Methods: We retrospectively reviewed TCA+ cases between 2014 and 2022. Preoperative ileostomy was performed when transanal bowel irrigation was ineffective. Radical surgery for TCA+ was performed at approximately 6 kg. The surgery was performed using laparoscopy through a multi-channel trocar with or without an additional 3-mm trocar and IPACA reconstruction with indocyanine green fluorescence angiography (ICG) to assess anastomotic perfusion and Lugol’s iodine staining to visualize the surgical anal canal. Results: Ten patients with TCA+ were included. Ileostomy was performed in seven cases. The median operation time and blood loss were 274.5 min and 20 mL, respectively. No significant postoperative complications were found. All patients experienced frequent liquid stools and perianal excoriation in the early postoperative period, requiring anti-flatulence or codeine. The median follow-up period was 3.5 years. Three patients required irrigation management 1 year postoperatively, and the others defecated a median of 3.5 times per day. The median Kelly’s clinical score was 5 in 5 patients aged ˃4 years. Conclusion: Reduced-port surgery, combined with Lugol’s iodine staining and ICG, was safe, feasible, and had cosmetically and clinically acceptable mid-term outcomes.